EFEKTIFITAS PEMBERIAN BUAH APEL MANALAGI DENGAN DOSIS BERVARIASI TERHADAP PENURUNAN KADAR GLUKOSA DARAH PADA PENDERITA DIABETES MELLITUS TIPE II DI KELOMPOK PROLANIS PUSKESMAS GENUK KOTA SEMARANG - Natanya Ayuhapsari; Wiwik Wijaningsih; Mohammad Jaelani (Poltekkes Kemenkes Semarang, 2018)
Background :Diabetes mellitus is a carbohydrate metabolism disorder characterized by an increased in blood glucose levels due to abnormal / decreased insulin work. Diet for people with diabetes mellitus is a food with a balanced composition between carbohydrates, protein, fat and fiber. Water soluble fiber namely pectin in apples is able to slowing the entry of glucose in the body. Objective : To know the effectiveness of giving apple manalagi with varying dose to decrease blood glucose level in type II diabetes mellitus in prolanis group of Puskesmas Genuk Semarang. Method: This research includes true experimental research with Randomized Pretest Posttest Control Group design and Complete Randomized Design study. Randomized sampling was 24 people for 4 treatment groups. Data collected were identity data, anthropometry, fasting blood glucose level and recall fiber intake by interview method and questionnaire. Result of analysis with One-Way ANOVA and ANOVA Repeated measure with α = 0,05. Result:There was a difference between fasting glucose levels before and after treatment in each treatment group (p=0,000). The most effective dose in lowering blood glucose levels is 2 x 200 grams. Conclusion: Giving of apples manalagi with a dose of 2 x 200 grams more effectively compared with a dose of 2 x 150 grams and 2 x 100 grams lowered fasting blood glucose levels in the study subjects. Apples manalagi can be used to help control blood glucose in diabetics.